Peran Becak Babel sebagai Komunitas Peduli Lingkungan dalam Pengembangan Nilai-nilai Civic Virtue Generasi Muda - Hijran, Muhamad; Suntara, Reza Adriantika (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
In facing global environmental challenges, the importance of developing civic virtues in the younger generation is increasingly crucial. Global environmental crises such as pollution, climate change and natural resource degradation require proactive action from various parties. However, the lack of environmental awareness and responsibility among the younger generation is a challenge in itself. This research discusses the role of the Becak Babel community in developing environmental awareness and civic virtue among the younger generation. This research uses a qualitative approach with a case study method to reveal how the role of the Babel Becak Community involves the younger generation in environmental care activities. The results of this research show that the Becak Babel community is a proactive agent of change in preserving the environment through sharing initiatives and educational programs such as tree planting, cleanliness campaigns and environmental education. This community has succeeded in instilling virtuous values such as social responsibility, active participation so that it has great potential in forming the character of the younger generation who care more about their environment.